ANTIBIOTIC RESISTANCE PATTERNS OF COMMON UROPATHOGENS ISOLATED FROM FEMALES AT ZAKHO CITY, KURDISTAN REGION, IRAQ. - ISSA, Fawzi Adil (Science Journal of University of Zakho, 2024)
Background: Urinary tract infection (UTI) is an infection in any part of the urinary system, including kidneys, ureters, bladder, and urethra. Uropathogenic bacterial-antibiotic resistance has become a severe challenge among UTI-causative agents. Objective: This work attempted to screen the activity of a wide range of antibiotics routinely used for UTI-derived infection management to assess the impact of antibiotics on some common UTI pathogens isolated from females. Method: This retrospective study was performed at Zakho Emergency Hospital, Kurdistan region of Iraq, from January 2016 to December 2019. Conventional bacteriological tests were used to identify the most common isolated uropathogens in females. The antibiotic sensitivity test was performed according to the Clinical and Laboratory Standards Institute (CLSI). The bacterial-antibiotics assay was determined using the disk diffusion (Kirby-Bauer) method, which depended on the microbiology laboratory records. Results: Out of 1730 urine samples, 1040 (60.4%) were found to be pathogens-positive samples. The most common uropathogens isolated were Staphylococcus spp 44% (n=460), Escherichia coli strains 25.35% (n=265), Klebsiella spp 15.78% (n=65), and Streptococcus spp 14.83 (n=155). Regarding the microbial-antibiotic resistance, ≤ 25% of the UTI investigated cases, except Streptococcus spp, meropenem, imipenem, and amikacin, showed a remarkable effect against all addressed pathogens. Vancomycin was the first choice against gram-positive bacteria in addition to rifampicin and doxycycline for Streptococcus spp. Gentamycin was found to be the most effective antimicrobial against Klebsiella spp. Concerning bacterial-antibiotic resistance ≥75% and excluding Streptococcus spp, amoxicillin, ampicillin/cloxacillin, erythromycin, clindamycin, cloxacillin, and metronidazole were completely non-functional against all bacteria. Azithromycin, norfloxacin, oxacillin, cefixime, nalidixic acid, and ceftazidime showed relatively weak activity against gram-positive bacteria in addition to cephalexin, ceftriaxone, and cloxacillin for Streptococcus spp. Ampicillin, augmentin, penicillin, and cephalexin were comparatively non-functional against gram-negative pathogens in addition to vancomycin, rifampicin, cephalothin, oxacillin, and trimethoprim for Klebsiella spp. All remaining antibiotics produced an activity ranging between ≥25% to ≤75% of examined cases. The results of this work may help clinicians to accurate their antibiotic-bacterial infection empirical treatment. Conclusion: All subjected bacteria exhibited a strong resistance to a broad spectrum of antibiotics. Therefore, except for imipenem, meropenem, or amikacin, an antibiotic sensitivity test should be conducted prior to prescribing any antibiotic.